Basic math - Siegel, Murray H.; Teaching Company (Chantilly, VA : Teaching Co., 1997)
Covers basic concepts of math, exponents, probability, algebra, statistics, and geometry.
Disc 4. Lesson 16. Adding and subtracting integers -- Lesson 17. Multiplication and division of integers, and and introduction to square roots -- Lesson 18. Negative and fractional powers -- Lesson 19. Geometry I -- Lesson 20. Geometry II -- Disc 5. Lessons 21. Graphing in the coordinate plane -- Lesson 22. Number theory -- Lesson 23. Number patterns I -- Lesson 24. Number patterns II -- Lesson 25. Statistics -- Disc 6. Lessons 26. Probability -- Lesson 27. Measurement -- Lesson 28. Problem solving techniques -- Lesson 29. Solving simple equations -- Lesson 30. Introduction to Algebra I.
DVD.
Instructor: Murray H. Siegel.
Copyright date on booklets is 1997 and 2005.
Keywords: Mathematics -- Study and teaching (Secondary)